PENGARUH PROFITABILITAS DAN MAKROEKONOMI TERHADAP NON-PERFORMING LOANS (Studi Empiris pada Perusahaan Perbankan yang terdaftar di BEI Periode 2017-2019) - Fajar Ihrom; Hersugondo Hersugondo (Faculty of Economic and Business Universitas STIKUBANK, 2021)
The study aims to find out the effect of ROA, ROA, CAR, BLIQ, CRISK, SIZE, INF, and GDP on NPL. This sampling technique uses purposive sampling. The sample used was 42 banks listed on the IDX with the 2017-2019 research period. The effect independent variable on the dependent variable is explained by using the multiple regression analysis methods. The classical assumption is also performed, namely normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The results showed that ROA, CAR and CRISK had a negative and significant effect on NPL, while BLIQ, SIZE, INF, and GDP had a negative and insignificant effect on NPL.